2020
DOI: 10.2108/zs200054
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocytes and Blattabacterium Endosymbionts of the German Cockroach Blattella germanica, the Forest Cockroach Blattella nipponica, and Other Cockroach Species

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…These endosymbionts are vertically transmitted from mother to offspring and play an important role in nitrogen cycling for their hosts [70][71][72]. Interestingly, a recent study reported the distribution patterns of Blattabacterium among wild and pest cockroach species and speculated this endosymbiont may participate in nitrogen metabolism differently due to the different diets and lifestyles of their respective hosts [73]. The closely…”
Section: Glossarymentioning
confidence: 99%
“…These endosymbionts are vertically transmitted from mother to offspring and play an important role in nitrogen cycling for their hosts [70][71][72]. Interestingly, a recent study reported the distribution patterns of Blattabacterium among wild and pest cockroach species and speculated this endosymbiont may participate in nitrogen metabolism differently due to the different diets and lifestyles of their respective hosts [73]. The closely…”
Section: Glossarymentioning
confidence: 99%
“…In many intimate gut microbial symbioses, specific symbionts are harbored extracellularly in a specialized gut region with tubular or pouch-like outgrowths, called midgut crypts or gastric ceca, in many stinkbugs, some beetles, fruit flies, and others ( 14 – 23 ). In many endocellular microbial symbioses, specific symbionts are hosted within the cytoplasm of specialized cells called bacteriocytes, which may constitute distinct organs called bacteriomes, in aphids and other hemipterans, lygaeid stinkbugs, weevils, grain beetles, tsetse flies, ants, cockroaches, and others ( 18 , 24 33 ). In addition, it should be noted that there are a variety of intermediate symbiotic configurations: for example, in anobiid beetles and leaf beetles, the symbiotic bacteria are located not only in the cavity of gastric ceca extracellularly but also within the cecal epithelial cells endocellularly ( 14 , 16 , 17 , 22 ), and in ants and tsetse flies, the bacteriocytes are localized to or embedded in a specific region of the midgut epithelium ( 24 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…To stabilize this association, specific cells, called bacteriocytes, evolved in the fat body. In B. germanica, single bacteriocytes are scattered in visceral fat bodies in the abdomen [68]. Their dispersed localizations avoid their isolation from the remaining fat body cells.…”
Section: Discussionmentioning
confidence: 99%